La interculturalidad en la educación de la Unidad Educativa Andoas en el Buen Vivir de los Estudiantes de la comunidad el Socorro, parroquia de Cubijíes, cantón Riobamba, provincia del Chimborazo. - Moyón Sani, Vilma Elizabeth (2018)
The research was carried out with the aim of identifying if the practice of interculturality in the education of the Educational Unit Andoas in the well-being of the students of the community "Relief" Cubijies parish of Riobamba canton, province of Chimborazo, in the study met the manifestations of one of the aspects dealt with as well as the development of the teachers in the institution. The problem occurs because teachers are based on knowledge creation, most do not promote the practice of interculturality and in the formation of core values that the human being should possess. The research was non-experimental because it is qualitative because it belongs to the study of the social sciences, the level of research was descriptive, documentary-bibliographical research, for this was taken into account 9 essential people of the institution(director, teachers, students and parents),using the technique of the interview whose instrument was the interview guide, in conclusion it was identified that in this institution if it is perceived interculturality through learning and teachers integrate all children in different educational activities.